Architecture of a unified split P‐shaped swarming metamaterial for thermal mutation. Issue 6 (24th April 2018) - Alam, Jubaer M.; Faruque, Mohammad R. I.; Hossain, Mohammad J.; Islam, Mohammad T.
Abstract: The article imparts the architecture of a compact and combined split P‐shaped metamaterial unit cell that is felicitous for dual band of microwave frequency and it shows negative permeability and permittivity at those frequencies. Two split P‐shaped resonators are connected to each other by a metal ink to increase the electrical length and two modified split‐ring resonators (SRR) reside inside each of it. The 10 × 10 mm 2 structure has been printed on FR‐4 and a correlation is made between the basic unit cell and array structures. An analogy was contrived on the performance after the analysis of unit cell and array structures to validate the performance of the proposed metamaterial. A great transmission coefficient having a band of 13 GHz with a 500 MHz band gap at the middle is demonstrated for all of these configurations. The effective parameters of the resonators cover C, X, and Ku‐band independently with double negative phenomena at X and Ku‐band with a frequency range of about 1.31 GHz. Having an auspicious design and wide range double negative characteristics, this structure can be applicable to convert radiation into usable form.